Divergent molecular responses of greater amberjack (Seriola dumerili) to acute salinity stress revealed by comparative transcriptome analysis - Liu, Yuqi; Yang, Yuchen; Qin, Ruotong; Peng, Yuhao; Huang, Yang; Zhu, Chunhua; Li, Guangli; Jiang, Dongneng; Shi, Hongjuan (Frontiers in Marine Science, 2023)
Greater amberjack (Seriola dumerili) is an important commercial fish for its high growth rate and excellent flesh quality, and sensitivity to variations of water salinity, which poses challenges to the cage culture. In this study, the greater amberjack were reared in the optimum salinity (30 ppt, CK) and undesired regimes (10 and 40 ppt) for 72 hours. The molecular adaptive mechanisms to salinity stress were revealed by the comparative transcriptome analysis for the gills and kidneys. In gills, a total of 445 and 423 differentially expressed genes (DEGs) were identified in 10 and 40 ppt salinity stress groups, respectively. Those DEGs were involved in cartilage and skeletal development, ions transport, and immune response. The major ion secretion and osmoregulation transport proteins gene slc12a2/nkcc1 and cftr expression levels were significantly down-regulated at 10 ppt, but slightly activated at 40 ppt, compared with the control group. The expression changes in response to the Na+, K+ movement, and Cl- ion secretion reduced under the hypo-osmotic exposure and ion excretion boost upon hyper-salinity stress. Meanwhile, the cartilage and skeletal development were enhanced in the gills by hypo- or hyper-salinity stimuli, which is critical for maintaining gill structures and improving respiration and osmoregulation under salinity stress. In kidneys, 600 and 539 DEGs were identified in 10 and 40 ppt groups, respectively. Those DEGs were enriched in oxygen transport, pronephros development, regulation of growth, blood coagulation, ion transmembrane transport, and immune response. While the known renal Na+/Cl– co-transporter gene slc12a3/ncc expression level was significantly down-regulated at 10 ppt, the organic cation transporter 2 gene slc22a2, ammonium transmembrane transport gene rhd and rhag expression levels were over-expressed under the hyper-salinity condition at 40 ppt, contributing to the salts secretion and ammonium transport regulation, to combat the osmotic influx of salts following the drink of seawater and elevated ammonia production upon high salinity stress. These findings advance our knowledge of adaptative mechanisms to the salinity stress and provide theoretical guidance for the optimal breeding mode for the aquaculture of the greater amberjack.